Clinical outcomes when applying NICE guidance for the investigation of recent-onset chest pain to a rapid-access chest pain clinic population. Issue 2 (12th September 2014) - Patterson, Caroline Marie; Nair, Arjun; Ahmed, Nabeel; Bryan, Leoni; Bell, Derek; Nicol, Edward David
Abstract : Objective: To describe the clinical outcomes of patients for whom National Institute for Health and Care Excellence (NICE) recent-onset chest pain guidance would not have recommended further investigation, compared with those of patients where further investigation would have been recommended. Methods: 557 consecutive patients with recent-onset chest pain attending rapid-access chest pain clinics (RACPC) in two district general hospitals over a 9-month period were retrospectively reviewed. Likelihood of coronary artery disease (CAD) was calculated according to NICE-defined modified Diamond–Forrester criteria. Patients were categorised into those for whom NICE guidelines recommend (NICE-Y) and do not recommend (NICE-N) further investigation. Main outcome measures were subsequent diagnosis of significant CAD and major adverse cardiac events (MACE) at 6 months. Results: 187/557 (33.6%) patients comprised NICE-Y group, with 370/557 (66.4%) in NICE-N group. 360/370 (97.3%) of NICE-N group would have been excluded from further investigation due to non-anginal chest pain. Of 92/557 (16.5%) patients subsequently diagnosed with significant CAD, 35/557 (9.5%) were from NICE-N group versus 57/557 (30.5%, p<0.0001) from NICE-Y group. Of 11 patients experiencing at least one MACE, 7/557 (1.9%) were from NICE-N group, versus 4/557 (2.1%, p=1.000) from NICE-Y group. Conclusions: The rigid application of NICE chest pain guidance to a RACPC population may result in up to two-thirds of patients being excluded from further cardiac investigation. Potentially, up to 10% of these patients may subsequently be diagnosed with significant CAD, with up to 2% potentially experiencing a major adverse cardiac event.